Peran Strategis Kebun Raya Dalam Konservasi Riset Dan Edukasi Lingkungan: Peran Strategis Kebun Raya Dalam Konservasi Riset Dan Edukasi Lingkungan - Irawanto, Rony (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
Indonesia is one of the world's centers of biodiversity but has a fairly high threat of extinction. The main causes of extinction include loss and habitat destruction. Therefore, a conservation strategy is needed in Indonesia. The purpose of this paper is to determine the conservation strategy in Indonesia, especially the Scientific Conservation Area (KKI) - Purwodadi Botanical Garden in managing conservation, research and environmental education. This research is descriptive narrative, starting in April 2024 through direct observation while at KKI - Purwodadi Botanical Garden (KRP) and also searching for references. KRP is one of the ex-situ plant conservation areas for the purposes of conservation, research, education, ecotourism and environmental services. Internationally, KRP is a Biosphere Reserve (CB). The Strategic Position of KRP in CB Bromo Tengger Semeru Arjuno is a conservation area whose existence is internationally recognized. However, the management of botanical gardens may need to be adjusted to the dynamics, needs and developments of the times. So it is necessary to create a new management flow and regulations, which are more relevant.